Appetite problem in cancer patients: Pathophysiology, diagnosis, and treatment. (2021) - Hariyanto, Timotius Ivan; Kurniawan, Andree
Highlights: GDF-15 and TLR4 have recently been found to be implicated in the pathogenesis of anorexia. Several questionnaires with different cut-off value can be used to diagnose anorexia in cancer. Anamorelin, mirtazapine, thalidomide, and EPA are new agents with promising effects in appetite. Abstract: Aim: This study aims to review the current evidence regarding appetite problem in cancer patients, mainly focusing on pathophysiology, diagnosis, and treatment. Introduction: Anorexia is the common symptom of malnutrition in cancer patients. Recently, the understanding of the pathophysiological mechanism of the appetite problem in cancer patients has been increasing that give impact to rigorous research to find the therapies for improving appetite in cancer patients. Discussion: The development of anorexia in cancer patients is a complex process that involves many cytokines, receptors, chemical mediators/substances, hormones, and peptides. Growth and differentiation factor-15 (GDF-15) and toll-like receptor (TLR-4) have recently been found to be implicated in the pathogenesis of anorexia. To help diagnose the appetite problem in cancer patients, several questionnaires can be used, starting from well-known questionnaires such as Functional Assessment of Anorexia Cachexia Therapy (FAACT), Visual Analog Scale (VAS), European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-QLQ30). Several drugs with different mechanisms of action have been studied to help in improving appetite in cancer patients. New repurposed agents such as anamorelin, mirtazapine, thalidomide, and eicosapentaenoic acid (EPA) have shown a beneficial effect in improving appetite and quality of life in cancer patients, however more phase 3 clinical trial studies is still needed. Conclusion: The pathophysiology of appetite problems in cancer patients is a complex process that involves many factors. Several drugs that target those factors have been studied, however more phase 3 clinical trial studies are needed to confirm the findings from previous studies.